Treatment And Recycling Of Water Ablution For Irrigation Purpose - Siti Nurnajwa, Ibrahim (2022)
A large amount of water is used in the ablution process, especially in musollas and mosques where greywater is permitted to stream freely and drain away. As quoted in the Hadith, Prophet Muhammad advised Muslims to avoid wasting anything, even when conducting the washing ritual or ablution before prayer. Most ablution systems in Malaysia consist of a row of water taps with a drainage through to take greywater to main drains. Because the tap is generally kept running, a lot of good water is squandered. In order to avoid wasteful waste, a simple recycling system may be developed to collect, purify, and reuse ablution water for non-portable water uses such as plant watering in a closed-loop system. This strategy not only introduces actual engineering solutions for encouraging sustainable living, but it also adheres to Islamic values of cautious use of natural resources. A research was done to create and test a conceptual model of the ablution water recycling system, named Eco-WUDHU, by referring to the University's own mosque. The Eco-Wudhu system, whether retrofitted or constructed from the ground up, represents a successful fusion of engineering know-how with religious principles for improved quality of life today and in the future.